Neurophysiological studies of patients with classical phenylketonuria: evaluation of results of IQ scores, EEG and evoked potentials - Coşkun, Turgay; Topçu, Meral; Üstündağ, İncilay and Özalp, İmran and Renda, Yavuz and Ciğer, Abdurrahman and Nurlu, Gülay (The Turkish Journal of Pediatrics, 1993)
Neurophysiological studies were conducted in 42 patients with classical phenylketonuria. The results of the intelligence quotient scores, electroencephalogram, visual evoked potentials and brain-stem auditory evoked potentials were evaluated. When compared with the controls, the subjects demonstrated a significant prolongation in VEP P₁ and BAEP I-V interpeak latencies and an increase in VEP N₁P₁ amplitudes. No relationship was found between these pathological responses and metabolic control. However, the observation of normal intelligence quotient scores in 14 out of 18 patients who displayed a pathological prolongation in P₁ latencies led us to the conclusion that evoked potentials may have a significant role in the determination of neurophysiological defects and that even cases with good metabolic control may have some obscure neurophysiological dysfunction which should be evaluated more carefully.